Contributions to the classification of North American Microctonus (Braconidae, Euphorinae) - Pucci, Thomas M. (Zootaxa, 2013)
The 31 species of Microctonus Wesmael that occur in North America are taxonomically treated. Six are described as new: M. cappilicrus, M. gouleti, M. passi, M. portalensis, M. rotundatus, and M. sharkeyi. Microctonus zimmermanni Loan is considered a junior synonym of M. brevipetiolatus (Thomson) and M. barri Loan is considered a junior synonym of M. muesebecki Loan. The European Perilitus alticae Haeselbarth is given the new name M. haeselbarthi. Microctonus nigritus (Provancher) is considered a nomen dubium. A key to the species, a list of hosts, and images are provided.